2010
DOI: 10.1159/000303041
|View full text |Cite
|
Sign up to set email alerts
|

KCNQ1 K<sup>+</sup> Channels are Involved in Lipopolysaccharide-induced Apoptosis of Distal Kidney Cells

Abstract: Most bacteria initiate host inflammatory responses through interactions with epithelial cells. Lipopolysaccharide (LPS), a component of the bacterial cell wall is a major cause of septic shock in emergency care units and in the pathogenesis of acute renal failure. Kidney cells exposed to LPS undergo apoptotic changes, including cell volume decrease, phosphatidylserine exposure, caspase-3- and membrane K+ conductance -activation. Whole-cell configuration was used to identify K+ channels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Several studies have observed a number of apoptotic tubular cells in LPS-induced acute kidney injury [37][38][39]. Indeed, VitD3 has an anti-apoptotic activity [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have observed a number of apoptotic tubular cells in LPS-induced acute kidney injury [37][38][39]. Indeed, VitD3 has an anti-apoptotic activity [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both stressors elicit injury in various tissues. LPS can activate K+ channels, leading to ion perturbation, increased intracellular cAMP, and apoptosis in kidney cells (8, 33), whereas increased intracellular cAMP in immune cells protects against DNA damage-induced apoptosis (34). Although it has been reported in the literature that radiation is able to detoxify LPS by destruction of the polysaccharide moieties and alteration of the lipid A component (35), the doses required far exceed what would be likely encountered in a radiological event.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar symptoms may be due to other factors. During infections, bacterial toxins, in particular lipopolysaccharide (LPS), have been demonstrated to induce nausea, vomiting and diarrhea, leading to acute renal failure, septic shock and death (8-11). LPS is found in the outer wall of Gram-negative bacteria, acts as an endotoxin, and elicits immune responses in animals by activating innate immune responses and triggering secretion of pro-inflammatory cytokines in various cells types (11-13).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Duranton et al (27) identified the ␤-subunit KCNE3 within cultured mouse DCT cells. Furthermore, they examined the involvement of KCNQ1-KCNE3 in the LPSinduced apoptosis of mouse DCT cells and revealed there is an activation of KCNQ1-KCNE3 conductance by LPS.…”
Section: Kcnj Gene Family Members In the Nephronmentioning
confidence: 99%